Occupants awareness in handling active fire protection system in low cost flat / Muhammad Iskandar Ismail - Ismail, Muhammad Iskandar (2012)
Most of the residents in low-cost flats are not aware of the safety of life, particularly in the event of fire. These problem from the past until today no one person or even relevant parties to solve the problem about the safety of low-cost flats for the fire-fighting. This study present the to identify the availability of the types and usage of meet the legal requirement active fire protection system in low cost flat. Secondly the purpose of this study is to study the occupant’s awareness and knowledge in handling active fire protection system and the lastly to purpose a system that can created awareness to occupants about the important active fire protection system in low cost flat. In carrying out this study, the authors have divided the analysis of the study into two parts, an analysis of the occupant in the flat and interview session with the head of the fire station and the Manager of Joint Management Body at the low cost flat. The awareness of the fire safety should begin with the occupants of the low cost flats with assistance of the fire and the bodies concerned about this.